Frameless stereotaxic radiosurgery for multiple brain metastases. - I. N. Diкаn; А. B. Griazov; Е. G. Аndreychenko; О. V. Zemskova; I. V. Кruchоk; М. М. Denisenko; I. P. Spasichenko (Medičnì Perspektivi, 2014)
Objective of this study was to retrospectively evaluate the effectiveness of frameless stereotaxic radiosurgery on LINAC for multiple (5–10) brain metastases and to identify prognostic factors related to survival and toxity. Materials and methods. 17 patients with multiple brain metastases, underwent frameless radiosurgery on Linac. The median tumors volume for radiosurgicaly treated lesions was 57 cm3 (range 20–94 cm3). The median prescribed radiation dose was 18 Gy (range 12–22 Gy). Univariate and multivariate analyses were used to determine significant prognostic factors affecting survival. Results. Overall median survival was 10 months after radiosurgery, and 1-year survival was 29,4%. Survival following radiosurgery was independent of patient’s age and sex, pretreatment of the cerebrum by using radiotherapy or surgery, number of brain metastases and their synchronization with the primary cancer, in contrast, survival was dependent on the patient's clinical performance score and extracranial tumor status. In multivariate regression analyses, the most important predictors associated with increased survival were KPS > or = 90 (P<0.023), and extracranial tumor status (P<0.004). Conclusions. LINAC frameless stereotaxic radiosurgery is effective method for multiple brain metastases treatment with good local control and acceptable toxicity. Karnofsky score (more than 90%), and extracranial tumor status before radiosurgery were good independent predictors of survival.